Investigation of Moderately Halophilic Bacteria Causing Deterioration of the Salted Sheep and Goat Skins and Their Extermination via Electric Current Applications - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2018)
Determination of moderately halophilic bacterial counts on the salted skins and examination of utilization of amino acid and carbon sources by skin isolates offer important information about biodegradation of salted skins. Hence, total counts of moderately halophilic bacteria, total counts of proteolytic and lipolytic moderately halophilic bacteria found on the salted sheep and goat skins belonging to different countries were examined in this study. One hundred-thirty seven moderately halophilic bacterial species closely related to species of genera Alkalibacillus, Bacillus, Chromohalobacter, Gracilibacillus, Halomonas, Idiomarina, Marinococcus, Oceanobacillus, Planococcus, Salimicrobium, Salinicoccus, Staphylococcus and Salinivibrio were used to detect utilization of different amino acids and carbon sources which are related to biodegradation of skins. The values of pH, moisture contents, ash contents and salt saturations of these skins were also investigated to understand the correlation between these parameters and moderately halophilic bacterial activities. All salted skin samples contained moderately halophilic bacteria, proteolytic and lipolytic moderately halophilic bacteria in high numbers. Each of 137 test isolates, obtained from the salted sheep and goat skins, used different amino acids found in the skin structure. While 100% of both sheep and goat skin isolates utilized L-arginine, 86%, 66%, 85%, 64% and 66% of the isolates respectively utilized L-glycine, L-alanine, L-tyrosine, L-proline and L-hydroxyproline amino acids. Ninety-three percent of the isolates used different carbon sources such as dulcitol (13%), D-sorbitol (29%), L-rhamnose (19%), ribose (52%), salicin (40%), myo-inositol (27%), xylitol (21%), benzoate (18%), propionate (34%), D-melezitose (31%), butanol (20%), propanol (23%), methanol (23%), formate (23%) and tartrate (12%). While pH values, moisture contents, ash contents and salt saturations of the sheep skins ranged from 6.53 to 8.01, 32 to 68%, 12 to 30% and 58 to 100%, respectively, the pH values, moisture contents, ash contents and salt saturations of the goat skins were between 6.65-8.06, 34-70%, 11-32% and 64-100%, respectively. The values of all skin samples were found to be suitable for the growth and catabolic activities of these bacteria. To prevent the growth and activities of moderately halophilic isolates causing skin deterioration, the annihilation effects of 0.5, 1.0, 1.5 and 2.0 A direct and alternating electric current treatments on the mixed culture of moderately halophilic isolates (Chromohalobacter israelensis, Chromohalobacter canadensis, Halomonas halodenitrificans, Staphylococcus nepalensis and Halomonas halmophila) were also separately investigated in the present study. Both 0.5, 1.0, 1.5, 2.0 A direct and alternating electric current applications used in this study completely annihilated the mixed culture of moderately halophilic spoilage microorganisms. As a conclusion, we suggest using low-level direct or alternating electric current treatment to eradicate harmful moderately halophilic bacteria in salt which will be used in brine curing of hides and skins in the leather industry.
Keywords: HIDE-SOAK LIQUORS; CURED HIDES; CATTLE HIDES; PRESERVATION; INACTIVATION; DIVERSITY; QUALITY; IDENTIFICATION; ENVIRONMENTS; ARCHAEA